The Incidence and Clinical Significance of Amiodarone and Acenocoumarol Interaction - Caraco, Yoseph; Chajek-Shaul, Tova (Thrombosis and Haemostasis, 1989)
Acenocoumarol sensitivity index (ASI) was calculated in 36 patients receiving amiodarone and acenocoumarol concomitantly, by dividing the acenocoumarol daily dose (μg kg−1 day−1) by the prothrombin ratio expressed as International Normalised Ratio (INR). It was found to be significantly lower (4.2 ± 0.3 pg kg−1 day−1) than the ASI (11 ± 0.6 μg kg−1 day−1) determined in 35 patients in the control group, who received acenocoumarol and not amiodarone. In 15 patients, ASI was 13.2 ± 1.4 and 4.2 ± 0.6 μg kg−1 day−1 before and after initiation of amiodarone therapy, respectively. In 5 patients, ASI was 6.2 ± 0.6 μg kg−1day−1, while patients were receiving both medications, and 28.1 ± 6.1 μg kg−1 day−1 following discontinuation of amiodarone therapy. ASI determined while patients were on both medications was not affected by the presence of mild impaired renal or liver function. In 7 patients treated with both drugs concomitantly, severe bleeding diathesis developed. It is concluded that amiodarone augmented the anticoagulant effect of acenocoumarol in all patients receiving both drugs. An initial reduction of acenocoumarol daily dose by 50% and further adjustment of acenocoumarol dose according to daily prothrombin ratio is recommended. It is also suggested that acenocoumarol dose should be adjusted after cessation of amiodarone therapy.
Keywords: Acenocoumarol; Amiodarone; Prothrombin ratio; Drug interaction